Making paddy cultivation profitable in Orissa - Das, Sandip (Indian Farming, 2015)
A farmer from Jajpur district inOrissa has turned his rice growingagricultural land into a profitablecommercial business by taking upfisheries and cultivation of fruits andvegetables. Because of the uniqueintegrated rice-fish system, developedby the Central Rice ResearchInstitute, farmers are making it surethat rice cultivation besides providingfood security also guaranteeslivelihood security.